CODE-SWITCHING IN MULTILINGUAL COMMUNITIES :CAUSES AND EFFECTS (The Conference Hub, 2025)
Code-switching is when people who speak more than one language or dialect alternate using those languages or dialects within a single conversation. This study examines the linguistic, social, psychological and cognitive factors that contribute to code-switching, as well as its impact on communication, identity, and language proficiency. Utilizing a qualitative approach, this research analyzes linguistic theories and real-world examples to explore the underlying motivations and consequences of code-switching. The findings suggest that code-switching serves as both a strategic and communication tool and a reflection of cultural and social dynamics. While it enhances linguistic flexibility and identity expression, it can also lead to linguistic insecurity and social stigma. These results highlight the need of viewing code-switching as a natural and systematic linguistic process rather than a deficiency in language competence.